Isolation and Characterization of Listeria monocytogenes Phage vB_LmoH_P61, a Phage With Biocontrol Potential on Different Food Matrices - Stone, Edel; Lhomet, Antoine; Neve, Horst; Grant, Irene R.; Campbell, Katrina; McAuliffe, Olivia (Frontiers in Sustainable Food Systems, 2020)
The high mortality rate associated with Listeria monocytogenes as well as its ability to adapt to the harsh conditions employed in food processing have ensured that this pathogen has become a significant concern in the ready-to-eat food industry. Lytic bacteriophages are viruses that hijack the metabolic mechanisms of their bacterial host as a means to grow and replicate, subsequently leading to host cell death due to lysis. This study reports the biological and genomic characterization of L. monocytogenes phage vB_LmoH_P61 (P61) and its potential application for the reduction of L. monocytogenes in artificially contaminated foods. Phage P61 is a virulent bacteriophage belonging to the family Herelleviridae and has a genome size of 136,485bp. The lytic spectrum of phage P61 was investigated and it was shown to infect serotypes 1/2a, 1/2b, 1/2c, 4b, 4e, and 6a. Treatment of artificially contaminated milk stored at 8 and 12°C with phage P61 resulted in a significant reduction in L. monocytogenes numbers over the product shelf life. Similarly, phage P61 reduced L. monocytogenes numbers on artificially contaminated baby spinach stored at 8, 12, and 25°C. The research findings indicate that biocontrol of L. monocytogenes with phage P61 may offer a safe and environmentally friendly approach for the reduction of L. monocytogenes numbers in certain ready-to-eat foods.